Crystal precipitation and dissolution in a porous medium: Evolving microstructure and perforated solid matrix - Schulz, Raphael (Special Topics and Reviews in Porous Media, 2019)
In this article, we derive an upscaled model for crystal precipitation and dissolution in a saturated porous medium with a perforated solid matrix. We model the solid matrix itself at the pore scale as a porous medium. Hence, we consider at the pore scale a Darcy-Stokes system, where the Beavers-Joseph boundary condition is proposed at the corresponding interface. By asymptotic expansions we derive an upscaled model describing the process via Darcy's law, a transport equation, and corresponding effective coefficients given by the evolution of the microstructure. Weak solvability of the upscaled model is also investigated.
CRIS-Team Scopus Importer:2019-10-04
Keywords: Beavers-Joseph boundary condition; Evolving microstructure; Fluid-solid interactions; Homogenization of PDE; Porous media